Long-term effect of tillage and crop rotation practices on soil C and N in the Swartland, Western Cape, South Africa - Cooper, Glen David (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.